Design of 2MHz OOK transmitter/receiver for inductive power and data transmission for biomedical implant - Abdelali El Boutahiri; Mounir Ouremchi; Ahmed Rahali; Mustapha El Alaoui; Fouad Farah; Karim El Khadiri; Ahmed Tahiri; Hassan Qjidaa (Institute of Advanced Engineering and Science, 2019)
In this work a 2 MHz on-off keying (OOK) transmitter/receiver for inductive power and data transmission for biomedical implant system is presented. Inductive link, driven by a Class E power amplifier (PA) is the most PA used to transfer data and power to the internal part of biomedical implant system. Proposed transmitter consists of a digital control oscillator (DCO) and a class E PA which uses OOK modulation to transfer both data and power to a biomedical implant. In proposing OOK transmitter when the transmitter sends binary value “0” the DCO and PA are turned off. With this architecture and 2 MHz carrier wave we have implemented a wireless data and power transfer link which can transmit data with data rate 1Mbps and bit error rate (BER) of 10-5. The efficiency of power transfer is 42% with a 12.7 uH transmitter coil and a 2.4 uH receiver coil and the power delivered to the load is about 104.7 mW. Proposed transmitter is designed for output power 4.1V. OOK receiver consists of an OOK demodulator, powered by rectified and regulated 5V p-p RF signal across the receiver coil. The supply voltage of proposed voltage regulator is 5 V with 9mV/V line regulation of. All circuits proposed in this paper were designed and simulated using Cadence in 0.18 um CMOS process.